Model estimations of possible climate changes of surface solar radiation at regional scales over Southern Africa and the South West Indian Ocean - (:unkn) unknown (My University, 2017)
Changes in Surface Solar Radiation (SSR) have the potential to significantly impact diverse aspects of the climate system, and notably the socio-economic development of any nation. To identify the possible impacts of climate change on SSR at regional scales (~50 km) over Southern Africa and the South West Indian Ocean (SA-SWIO; 0-40°S ; 0- 100°E) up to the end of the 21st century, a slice downscaling experiment consisting of simulations covering three temporal windows: a) the present 1996-2005; b) the future 2046-2055 and 2090-2099 conducted with the Regional Climate Model (RCM) RegCM version 4, driven by the European Center for Medium-range Weather Forecasting (ECMWF) ERA-Interim reanalysis (ERAINT, only present) and 2 Global Climate Model (GCMs: HadGEM2-ES and GFDL-ESM2M) from the Coupled Model Intercomparison Project Phase 5 (CMIP5) under RCP8.5 scenario, are performed and evaluated. Since the slice simulation is of limited temporal coverage, number of regional and driven global models and climate change forcings, mainly because of the limit of available computational resources, the study towards a comprehensive knowledge of SSR changes in context of climate change is thus extended: an ensemble consisting of outputs from 20 regional climate downscaling realisations based on 5 RCMs that participated in the Coordinated Regional Downscaling Experiment (CORDEX) program (CORDEX-Africa) along with their 10 driving GCMs from CMIP5 covering southern Africa (0-40°S; 0- 100°E) during the period of 1990-2099 is analyzed under RCP4.5 and RCP8.5 up to 2099.The slice experiment indicates that 1) RegCM4 simulates present-day seasonal climatology, (surface air temperature, precipitation and SSR) quite well, but has a negative total cloud cover bias (about -20% in absolute percentage) when forced by the ERAINT and the two GCMs. 2) Internal variability of RegCM4-simulated annual means SSR (about 0.2 W/m2) is of one order smaller than the model bias compared with
Keywords: African Research